The green algorithm: can sustainability define the winner in the AI race? - Rivero-Silva, Sebastián; Chinarro Vadillo, David; Prieto-Andres, Antonio (Frontiers in Political Science, 2025)
This article explores whether environmental sustainability may become a strategic axis in the evolving AI rivalry between China and the United States. By comparing ChatGPT and DeepSeek, it examines how ecological efficiency, data sovereignty, and infrastructural autonomy intersect with national AI strategies. While ChatGPT remain cloud-dependent and resource-intensive, DeepSeek—according to unverified developer data—prioritizes offline deployment and energy-efficient design, aligning with China's pursuit of techno-sovereignty. Still, potential ecological gains may be undermined by online variants or outdated hardware. Also, the literature highlights security risks associated with DeepSeek's distilled models. This analysis, grounded in a case study that is not fully representative but rather illustrative, shows that sustainability is no longer peripheral but increasingly regarded as an important element of geopolitical agendas. Although it remains premature to conclude that it is a decisive axis of technological competition, current evidence suggests a gradual reframing of strategic priorities toward more responsible innovation.